Integrated metabolomic, lipidomic and proteomic analysis define the metabolic changes occurring in curled areas in leaves with leaf peach curl disease - Novello, María Angelina; Bustamante, Claudia Anabel; Svetaz, Laura; Goldy, Camila; Valentini, Gabriel Hugo; Drincovich, María Fabiana; Brotman, Yadiv; Fernie, Alisdair R.; Lara, María Valeria (Wiley, 2024)
Peach Leaf Curl Disease, caused by the fungus Taphrina deformans, is characterized by reddish hypertrophic and hyperplasic leaf areas. To comprehend the biochemical imbalances caused by the disease an integrated approach including metabolomics, lipidomics, proteomics and complementary biochemical techniques was undertaken. Symptomatic and asymptomatic areas were dissected from leaves with increasing extension of the disease. A differential metabolic behaviour was identified in symptomatic areas with respect to either asymptomatic areas or healthy leaves. Symptomatic areas showed an altered chloroplastic functioning and composition which differs from the typical senescence process and includes decrease in the photosynthetic machinery, alteration in plastidic lipids, and decreased starch, carotenoid and chlorophyll biosynthesis. In symptomatic areas, alteration in redox-homeostasis proteins and in triacylglycerols content, peroxidation and double bond index were observed. Proteomic data revealed induction of host enzymes involved in auxin and jasmonate biosynthesis together with up-regulation of phenylpropanoid and mevalonate pathways and down-regulation of the plastidic methylerythritol phosphate route. Amino acid pools were affected, with up-regulation of proteins involved in asparagine synthesis. Overall, we conclude that curled areas exhibited a metabolic shift towards functioning as a sink tissue importing sugars and producing energy through fermentation and respiration and reductive power via the pentose phosphate route.